2014
DOI: 10.1097/qai.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Mental, Neurological, and Substance Use Disorders in People Living With HIV/AIDS in Low- and Middle-Income Countries

Abstract: Depression, alcohol use disorders (AUD), and neurocognitive disorders are the 3 most prevalent mental, neurological, and substance use disorders in people living with HIV infection in low- and middle-income countries (LMICs). Importantly, they have an impact on everyday functions and on HIV outcomes. Many LMICs have validated tools to screen for and diagnose depression and AUD in the general population that can be used among people living with HIV infection. Current screening and diagnostic methods for HIV-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
87
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 126 publications
4
87
2
1
Order By: Relevance
“…A recent study of current depression among recently-diagnosed men who have sex with men (MSM) found 36% prevalence of depression, (26) in line with our finding of 34% depression prevalence among recently-diagnosed patients. People who inject drugs had the highest prevalence of depression and anxiety, in line with a rich literature documenting the comorbidities of mental health and substance use (4, 27, 28). …”
Section: Discussionsupporting
confidence: 67%
“…A recent study of current depression among recently-diagnosed men who have sex with men (MSM) found 36% prevalence of depression, (26) in line with our finding of 34% depression prevalence among recently-diagnosed patients. People who inject drugs had the highest prevalence of depression and anxiety, in line with a rich literature documenting the comorbidities of mental health and substance use (4, 27, 28). …”
Section: Discussionsupporting
confidence: 67%
“…(19,20) In addition, some patients stop taking the medicines to drink alcoholic beverages on weekends; (23) consequently, they do not reach complete viral suppression and are more susceptible to viral resistance. (24) In general, alcohol use is a strong predictor of drug adherence failures, and worsens the clinical outcome of PLWHA. (2,16,25) The consumption of alcohol and other substances that cause dependence in PLWHA can trigger competition and interactions with antiretrovirals, and change their binding protein, because ethanol competes with the drugs in the isoenzyme linkages of the metabolization process.…”
Section: Discussionmentioning
confidence: 99%
“…These neurological disorders afflict a substantial proportion of HIV-infected individuals, with estimates ranging from 20–60% despite access to cART (Robertson et al 2007; Heaton et al 2010; Chibanda et al 2014; Ances and Ellis 2007). Furthermore, cognitive impairment and depression are risk factors for each other, decrease cART compliance, and are associated with a faster progression to AIDS and mortality (Chibanda et al 2014; Del Guerra et al 2013). Enhanced catabolism of tryptophan (TRP) through the kynurenine pathway (KP) may contribute to the etiology of both of these disorders by generating neurotoxic levels of KP metabolites and diverting TRP away from serotonin synthesis, though evidence in brain tissue has remained limited.…”
Section: Introductionmentioning
confidence: 99%